A case of COVID-19 diagnosed with favipiravir-induced drug fever based on a positive drug-induced lymphocyte stimulation test. (May 2021) - Murai, Yushi; Kawasuji, Hitoshi; Takegoshi, Yusuke; Kaneda, Makito; Kimoto, Kou; Ueno, Akitoshi; Miyajima, Yuki; Kawago, Koyomi; Fukui, Yasutaka; Ogami, Chika; Sakamaki, Ippei; Tsuji, Yasuhiro; et al.
Highlights: We report a case of COVID-19 diagnosed with favipiravir-induced drug fever. Drug-induced lymphocyte stimulation test (DLST) was positive for favipiravir. A decrease in serum favipiravir concentration was observed along with fever resolution. Differential diagnosis of fever in COVID-19 on favipiravir should include drug fever. Abstract: As of October 2020, there is still no specific drug to treat COVID-19 as it rages worldwide. Favipiravir, indicated for the treatment of new and re-emerging influenza infections, has been suggested to be effective against SARS-CoV-2, although this is not yet fully validated. We administered favipiravir to a 64-year-old female patient with COVID-19. Her symptoms resolved quickly after the start of treatment, with reduction of SARS-CoV-2 viral load, but she developed a fever again on day 12. Since the fever was relieved by discontinuation of favipiravir, and based on positive results with a drug-induced lymphocyte stimulation test, we diagnosed her with favipiravir-induced drug fever. A decrease in the serum concentration of favipiravir was observed along with resolution of the fever. The present case suggests that drug fever should be considered in the differential diagnosis of relapsing fever episodes in COVID-19 patients receiving favipiravir.